Management approach of patients with violent and aggressive behaviour in a district hospital setting in South Africa - Oladele V. Adeniyi; Ntandazo Puzi (South African Family Practice)
Aggressive and violent behaviour is very common in the hospital setting. Simple agitation may unpredictably progress to overt aggression and violence by any patient in the emergency centres (ECs). Aggressive behaviour often manifests in forms of verbally abusive language, verbal threats and intimidating physical behaviour. Violent behaviour comprises the intentional use of physical force or power, threatened or actual, against self (suicidal), or another (homicidal) or properties, group or community, that could potentially result in injuries, death, psychological harm or deprivation. Therefore, individuals with unusual agitation and aggression should be treated as an emergency in both the community and healthcare settings in order to mitigate the progression to physical violence. Whilst the incidence and prevalence of aggressive and violent behaviour are higher in individuals with an underlying mental disorder, substance use disorder or comorbid mental disorder and substance use disorder, other individuals can also present with these behaviours in the ECs. Therefore, the front-line clinicians must be knowledgeable and competent in managing patients with aggressive behaviour with a view to de-escalate the situation and preventing or curtailing violence. This paper presents an evidence-based approach for managing patients with aggressive and violent behaviour, including a review of the steps for admitting patients for assisted or involuntary care.